2002
DOI: 10.1890/0012-9658(2002)083[2328:cfpbai]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Pollination Between an Invasive Species (Purple Loosestrife) and a Native Congener

Abstract: Invasive species are frequently regarded as superlative competitors that can vegetatively crowd out natives, but little is known about whether invasives can compete for pollination services with native plants. We hypothesized that, when the showy invasive species Lythrum salicaria (purple loosestrife) was present, pollinator visitation and seed set would be reduced in a native congener, L. alatum (winged loosestrife). To test this hypothesis, we constructed mixed and monospecific plots of the two species. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(175 citation statements)
references
References 46 publications
7
166
0
2
Order By: Relevance
“…An example of the latter is B. chrysophyla ("murici" with oil and pollen as reward), on whose fl owers we observed bees not found visiting D. kunthii, but many visitors of Davilla were seen foraging on B. chrysophyla. Furthermore, several authors point out that inter-plant competition may diminish the quantity and quality of pollen deposited on co-specifi c stigmas, as constancy of visitors is aff ected (Harder & Barret 1996;Caruso 1999;Brown et al 2002). Working on mono-specifi c and mixed environments, Bell et al (2005) found 42% plant-plant and 10% inter-specifi cally fl ower-fl ower movement in mixed environments, which greatly decreased the pollination effi ciency at this site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of the latter is B. chrysophyla ("murici" with oil and pollen as reward), on whose fl owers we observed bees not found visiting D. kunthii, but many visitors of Davilla were seen foraging on B. chrysophyla. Furthermore, several authors point out that inter-plant competition may diminish the quantity and quality of pollen deposited on co-specifi c stigmas, as constancy of visitors is aff ected (Harder & Barret 1996;Caruso 1999;Brown et al 2002). Working on mono-specifi c and mixed environments, Bell et al (2005) found 42% plant-plant and 10% inter-specifi cally fl ower-fl ower movement in mixed environments, which greatly decreased the pollination effi ciency at this site.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, that competition may occur due to the preferences of the pollinator or inappropriate pollen transfer (Bell et al 2005). Th e fi rst case occurs when a more attractive plant draws visitors away from other plants, whose reproductive successive is consequently negatively aff ected (Waser 1983;Sih & Baltus 1987;Brown et al 2002). Th e inappropriate transfer of pollen occurs when heterospecifi c pollen is deposited on the stigma of one or more competitors, similarly decreasing seed set (Rathcke 1983;Brown & Mitchell 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Invasive plants can outcompete native species for pollination services, which results in the local decline of native populations. For example, purple loosestrife, a weed introduced to North America, has been reducing both the pollinator visitation and subsequent seed set of a native congener (Brown et al 2002).…”
Section: Responses Of Generalized Mutualisms To Threatsmentioning
confidence: 99%
“…In other words, invasion is determined by characteristics of the introduced species (driving their invasiveness) and by characteristics of the native recipient community (driving its invasibility; Richardson and Pysek 2006). Introduced species that successfully invade native communities are frequently regarded as strong competitors (Blossey and Nötzold 1995;Brown et al 2002), and there is increasing evidence that several below-ground processes, such as root foraging and interactions with soil microbes, contribute to the outcome of competition (e.g. Klironomos 2002;Aschehoug et al 2014;Keser et al 2015).…”
Section: Introductionmentioning
confidence: 99%